Research handbook of financial markets - Gurkaynak, Refet S.; Wright, Jonathan H. (Research handbooks in money and finance series, 2023)
"The Research Handbook of Financial Markets carefully discusses the histories and current states of the most important financial markets and institutions, as well as explicitly underscoring open questions that need study. By describing the institutional structure of different markets and highlighting recent changes within them, it accurately highlights their evolving nature. Taking the perspective that finance and macroeconomics are intertwined, this illuminating Research Handbook brings together prominent experts to investigate key market interactions. Chapters act as self-contained case studies of particular markets, allowing for a thorough individual examination of each. Ultimately, they offer a holistic understanding of financial markets and the current state of research. Academics and researchers in economics and finance curious about developments within financial regulation and banking will find this comprehensive Research Handbook to be hugely valuable. Market participants will additionally find it to be a useful reference, along with regulators seeking to mitigate financial instability"--